The Bureaucracy of Nazi Germany (1933-1939): A Political and Legal Paradigm - Palamarchuk, Evgenii A.; Mordovtsev, Andrey Yu.; Mordovtseva, Tatiana V.; Shaliapin, Sergei O.; Pozdniakov, Ilia P. (Journal of History Culture and Art Research, 2019)
The article is devoted to the analysis of the main legislative acts adopted in Nazi Germany between 1933 and 1939 that determined the legal status of civil servants in the Third Reich and regulated all aspects of their life and work. The main aspects of the problem are considered in terms of various approaches to the selection of criteria for legal progress, which actualizes the stated topic and allows considering the aspects of the legal life of the Third Reich previously neglected by researchers. The present work particularly focuses on the policy of Nazification of the public service sector, i.e. the racial component of the development strategy of Nazi bureaucratic law, in particular the discriminatory provisions of the Law on the Restoration of Professional Bureaucracy of 1933 and the Law on German Bureaucracy of 1937, on the basis of which access to the bureaucracy was closed to representatives of the "non-Aryan" population of Germany. Emphasis is put on the fact that, despite the dissatisfaction of part of the bureaucracy with their financial situation and lengthening of the working week, most public servants remained faithful to the regime throughout its existence, acting as a reliable support.